Linguistic Theory in the Practical Lexicography of the African Languages - Chabata, Emmanuel (Lexikos, 2009)
Abstract: In this article, we look at the relationship between linguistics and lexicography. We specifically look at the relevance of data derived from theoretical linguistic investigations to the compilation of diction-aries in African languages. Our point of departure is that since it is language description that lies at the core of both lexicography and linguistic theory, lexicographers can improve their work by using insights from theoretically-guided linguistic investigations. Our view is that as long as lexicographers focus on words and their existence in the linguistic system, they cannot work effectively without referring to linguistic theory, consciously or unconsciously. Lexicography is not only concerned with dictionary creation, that is, with the collection of lexical units and their proper description in dictionary entries, but also with the theoretical aspects concerning the lexicon. It is necessary for dictionaries to capture all lexical interrelationships of a phonetic, morphological, syntactic or semantic nature. Drawing examples from a few dictionaries on African languages, we try to show how dictionary compilers have benefited from specific theoretical investigations in general linguistics. We look at how the different linguistic theories have contributed to the improvement in the quality of the contents of some dictionaries of African languages. Our conclusion is that there is a stronger bond between linguistic theory and lexicographic practice than is generally assumed. Ways must therefore be found to understand the various links between the two disciplines. There should be a deliberate move from mutual neglect to collaboration between the two disciplines.